EFEKTIVITAS PROGRAM EDUKASI KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN PHBS PADA SATUAN KOMUNITAS PRAMUKA INKLUSI KOTA MALANG - djuwadi, ganif; Sunindya, Bernadus R. (Jurnal Informasi Kesehatan Indonesia (JIKI), 2024)
Healthy Indonesia Program with a Family Approach (PIS-PK), which emphasizes the importance of providing health education for all levels of society, including vulnerable groups such as people with disabilities. This study aims to evaluate the effectiveness of a health education program in improving knowledge of Clean and Healthy Living Behavior (PHBS) among members of the Inclusive Scout Community Unit in Malang City. The study employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 32 participants with disabilities, aged 12–17 years, participated in the three-day health education program, which included lectures, discussions, demonstrations, and hands-on practice in five main aspects of PHBS. Data were collected using validated questionnaires administered during pre-test and post-test phases and analyzed using the Wilcoxon signed-rank test to evaluate score changes. The results showed a significant increase in post-test average scores across all assessed aspects, with effect size values ranging from 0.59 to 0.62, indicating substantial practical impact. The largest improvements were observed in the Basic Life Support (BLS) and Healthy Food aspects, with post-test average scores reaching 8.19. These findings confirm that the health education program effectively enhanced participants' health literacy, particularly through interactive and participatory learning approaches. This study provides a concrete solution to the issue of low health literacy among individuals with disabilities and presents a model that can be applied in other communities. It is recommended that similar programs be implemented over a longer duration or incorporate digital technology to support sustainable learning. These findings offer valuable insights for the development of inclusive health education models tailored to local needs.